Optimizing Tourism Potential to Improve Regional Economy in Langkat Regency - Riana, Zenni; Pane, Sri Gustina; Yusrita, Yusrita; Mirza, Teuku (Medan Resource Center, 2024)
This study explores efforts to optimize tourism potential to improve the regional economy in Langkat Regency, North Sumatra. With abundant natural and cultural potential, such as Gunung Leuser National Park and Bukit Lawang, Langkat has a great opportunity to develop as a leading tourist destination. This study uses a qualitative method with a case study approach, involving in-depth interviews, observations, and documentation analysis. The results of the study show that, despite having great potential, Langkat Regency still faces various challenges, including limited infrastructure, lack of tourism promotion, and low local community participation. Inadequate infrastructure is the main obstacle in tourism development, while limited promotion results in low awareness of tourists' tourism potential. The active participation of local communities needs to be increased through empowerment and education, so that the economic benefits of tourism can be felt equally. The conclusion of this study emphasizes the importance of careful planning, infrastructure improvement, and effective promotion strategies to optimize the tourism potential of Langkat, which in turn can encourage sustainable regional economic growth.